Robotic surgeries for patients with colorectal cancer who have undergone abdominal procedures: Protocol for meta-analysis. Issue 15 (April 2018) - Hu, Ming; Miao, Changfeng; Wang, Xiaopeng; Ma, Yuntao
Abstract: Background: Although the safety and the advantages of laparoscopic and robotic colorectal surgeries have been confirmed, the use of both modalities in patients with previous abdominal surgeries (PAS) history remains uncertain. Herein, we perform a meta-analysis to investigate the impact of PAS on perioperative recovery outcomes from laparoscopic and robotic colorectal surgeries. Methods: We will search PUBMED, the Cochrane Library, the Chinese Biomedical database (CBM), WanFang data, China National Knowledge Infrastructure (CNKI) up to January 2018. Studies will be screened by title, abstract, and full text independently and in duplicate. Studies that report the impact of PAS on perioperative recovery outcomes from laparoscopic and robotic colorectal surgeries will be eligible for inclusion. Outcome variables will be assessed included combined resection, conversion, operation time, blood loss, number of retrieved lymph nodes, days to soft diet intake, length of hospital stay, and postoperative complications. Assessment of risk of bias and data synthesis will be performed using STATA SE 12.0. Heterogeneity among studies will be assessed using the I 2 statistic. Results: Randomized controlled trials, prospective cohort studies, and propensity-matched comparative studies will be used for the quantitative synthesis of the meta-analysis to evaluate the impact of PAS on perioperative recovery outcomes from laparoscopic and robotic colorectal surgeries. Conclusions: We aim to draw an objective conclusion of the comparisons in aspects of perioperative outcomes and provide physicians level I evidences for clinical decision makings.